Safflower (n-6) and flaxseed (n-3) high-fat diets differentially regulate hypothalamic fatty acid profiles, gene expression, and insulin signalling. (January 2018) - Fernandes, Maria Fernanda; Tache, Maria Cristina; Klingel, Shannon L.; Leri, Francesco; Mutch, David M.
Abstract: Polyunsaturated fatty acids (PUFA) have important signalling roles in the hypothalamus, a region of the brain that regulates whole-body energy homeostasis. While evidence suggests that high PUFA intake can impact hypothalamic activity, the underlying molecular mechanisms regulated by essential dietary n-6 and n-3 PUFA (i.e., linoleic acid and α-linolenic acid, respectively) remain poorly described in this brain region. To differentiate the roles of essential dietary PUFA on hypothalamic function, we fed male rats high-fat diets (35% kcal/d) containing either safflower (linoleic acid) or flaxseed (α-linolenic acid) oil for 2 months. Control rats were fed a low-fat (16% kcal/d) diet containing soybean oil. Hypothalamic fatty acids and gene expression were investigated by gas chromatography and microarray, respectively. Safflower-fed rats had higher total n-6 PUFA content due to increases in linoleic acid, arachidonic acid, and osbond acid compared to the other diet groups, while flaxseed-fed rats had higher total n-3 content due to increases in α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid. Safflower-fed rats showed augmented expression of genes related to hypothalamic insulin signalling compared to controls. This was mirrored by significant increases in phosphorylated AKT thr308 and AKT ser473 levels; indicative of increased PI(3)K/AKT pathway activity. These changes were not observed in the hypothalamus of flaxseed-fed rats. Our findings provide new molecular insights into how essential fatty acids influence the hypothalamus and, potentially, whole-body energy homeostasis. This work also provides new knowledge to better understand the impact of essential fatty acids on metabolic and behavioral phenotypes. Highlights: High-fat diets containing either safflower (n-6) or flaxseed (n-3) oil were studied. The diets differentially altered hypothalamic fatty acid content. Global gene expression was strongly influenced by the safflower diet. Hypothalamic insulin signalling was activated by the safflower diet. The flaxseed diet did not influence gene expression or insulin signalling.